“Codicology Manuscript Works Of Fiqh Written In Maverannahr Under The Name “Al-Muhit” (Texas Journal of Philology, Culture and History, 2024)
This article inform about manuscripts books is wrote under the name “al-Muhit”, it can be stated that the work “al-Muhit al-Burhani” and “al-Muhit al-Sarakhsi” had served as a main legal source in Islamic world, particularly, in the Hanafi madhhab spread countries. The fact that copies of the work had widely been spread in Turkey denotes that the work had been under great attention of the Hanafi ulama.